Rents And the Cost and Optimal Design of Commodity Taxes - Perroni, Carlo; Whalley, John (The Review of Economics and Statistics, 1998)
This paper numerically investigates the significance of rents for both the welfare costs and the optimal design of commodity taxes using a general-equilibrium model calibrated to 1986 Canadian data. In the data we use, Ricardian rents are concentrated in agriculture and utilities, with market structure rents concentrated in manufacturing. Different types of rents have different implications for the welfare cost of taxes, and hence also for appropriate tax design. Ricardian rents lower the cost of taxes; rents supported by imperfect competition (with no free entry) raise the cost of taxes; rents supported by regulation generate rent-seeking costs, and if taxed improve resource allocation. Model results show a markedly nonuniform optimal tax structure, and a substantial influence of the treatment of rents on the pattern of optimal tax rates by commodity.